A southern North Sea Miocene dinoflagellate cyst zonation: - Munsterman, D.K.; Brinkhuis, H. (2004)
An integrated stratigraphical analysis emphasizing organic-walled dinoflagellate cyst (dinocyst) distribution has been carried out on multiple boreholes penetrating the Miocene in the subsurface of the Netherlands (southern North Sea Basin). The bulk of the investigated successions is attributed to the Breda Formation, a regional lithostatigraphical unit most complete in the south-eastern part of the Netherlands. In concert with a first regional integrated bio (chrono) sequence-stratigraphical framework, fourteen informal dinocyst zones for the southern North Sea Miocene (SNSM), and three subzones are proposed for the Breda Formation. By also integrating (chrono)stratigraphic information from Mediterranean and North Atlantic dinocyst studies a first ever detailed age-model is here proposed for the Miocene in the subsurface of the Netherlands.